Teacher evaluation as an onto-epistemic framework - Holloway, Jessica (British journal of sociology of education, 2019)
This article analyzes the constitutive and productive effects of one US middle school's teacher evaluation system, and the way it operates to (re)make teacher subjects. Using transcripts from interviews with teachers and evaluators, as well as policy and system protocol documents, the article demonstrates how a positive evaluation discourse has become the structuring framework for legitimizing high-stakes evaluation, normalizing constant surveillance and audit, and producing new teacher subjects who assemble themselves as perpetually imperfect. The article illustrates how the evaluation system has produced a culture of compliance where the teacher's professional and ethical identity is constituted by the tools, practices, and norms of evaluation. It argues that the evaluation system is an onto-epistemic regime that fundamentally reconstitutes the purpose, identity, and function of the teacher subject. This article raises new questions about who a teacher can be, what types of attitudes can be imagined, and what actions can be exercised.